DRIFT SPECTROMETRY: TRADITIONAL METHODS AND THEIR DEVELOPMENT PROSPECTS - V. I. Kapustin; A. P. Korzhavyi (Российский технологический журнал)
A brief review of the traditional drift-spectrometry methods has been given: time-of-flight ionic mobility spectrometry, ionic mobility incrementation spectrometry, tandem drift-spectrometry of various modifications.Well-known information on surface-ionized drift-spectrometry has been given from the related papers and this method main trends advantages comparing with the available ones have been formulated.